TOPOLOGY OPTIMIZATION OF STRUCTURES USING HYBRID CELLULAR AUTOMATION METHOD BASED ON RELIABILITY - SHEN YaDong; FENG JianHu; WANG XunTao; CHENG XiaoHan (Jixie qiangdu)
In order to suppress gray-scale elements in Hybrid Cellular Automation method, distance factor and a new updating technique for state variables are proposed, combining the uncertainty of engineering structure, the optimization model of structural topology is established based on reliability. First, the modified random variables could be obtained through the reliability analysis, the reliability constraints are translated into deterministic constraints, and then the modified random variables are used for deterministic structural topology optimization. The optimization results under different updating techniques are contrasted. Results show that the proposed updating technique for state variables can effectively reduce the amount of gray-scale elements and reduce the strain energy of the structure.